Mathematical modeling of the influence of thermal power station in aquat- ic environment when cooled condensers (Journal of Mathematics Mechanics and Computer Science, 2011)
This paper presents the mathematical model of the thermal power station influence in the aquatic environment, which is solved by the Navier - Stokes and temperature equations for an incompressible fluid in a stratifiedmedium based on the method of splitting into physical parameters which are approximated by finite-difference method.